CELEBRATING 30 YEARS OF EXCELLENCE: A TRIBUTE TO AUTHORS AND REVIEWERS OF THE INTERNATIONAL JOURNAL OF INDUSTRIAL ENGINEERING: THEORY, APPLICATIONS AND PRACTICE - Lee, Gyu M. (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
As we stand on the cusp of the 30th anniversary of the International Journal of Industrial Engineering: Theory, Applications and Practice (we call it “the Journal”), it is a moment to celebrate its remarkable journey and acknowledge the vital roles played by its authors and reviewers. From its inception, the Journal has evolved into a leading international journal renowned for its commitment to publishing high-quality research that has significantly impacted the field of industrial and manufacturing engineering. The Journal's scope encompasses a broad spectrum of industrial engineering disciplines. This comprehensive approach ensures that the Journal remains at the forefront of industrial engineering research and continues to serve as a valuable resource for both scholars and practitioners in the field.